Evaluation of adnexal masses: correlation of clinical examination, sonographic assessment and histopathological findings - Ray, Sreeparna; Halder, Sanjana; Saha, Manas K.; Kyal, Amit; Chowdhury, Srijoni (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Prevalence of symptomatic adnexal masses is 1:1000 in premenopausal women and 3:1000 in post –menopausal women. Benign diseases of ovaries and fallopian tube are commonest etiology. However, as risk of neoplastic lesions increases with age and further after menopause The primary goal of diagnostic evaluation of adnexal masses is to exclude malignancy. Methods: This one-year prospective observational study was carried out on 100 female patients attending gynaecology OPD with the clinical diagnosis of adnexal mass. Female patients presenting with symptoms like lower abdominal pain, menstrual irregularity and palpable mass or asymptomatic patients with incidental finding of adnexal mass were included in the study. The aim of the study was to compare the sensitivity, specificity and predictive value of clinical examination, ultrasonography and to compare it with the histopathology. Results: Ultrasound of pelvis was done for all patients. Laparotomy was done for all cases and the specimen was sent for histopathological examination. 70% tumours were benign and 30% tumours were malignant. As per our study, ultrasonography has the highest diagnostic accuracy (93%) followed by pelvic examination (86%) and RMI score (86%). Clinical examination has highest sensitivity of 93.33% followed by CA-125 (86.66%) and ultrasonography (83.33%). Conclusions: Thus, ultrasound is the primary modality used for detection and delineation of pelvic masses. The study also showed that RMI has better performance than CA 125 in the prediction of malignancy. Thus, with such simple methods we can diagnose precisely without advanced radiological imaging.